If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -1 + -6 Combine like terms: -1 + -6 = -7 y = -7 Solving y = -7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -7
| 20x^3+13x^2+2=0 | | -5-(2-3p)= | | 1.4q-4.7-1.9q=-1.5q-4.8 | | (p+3)/2=(p-4)/3 | | x+x+1+x+2=246 | | -.05(80)+.7x=.3(80+x) | | 18.1-x=-0.7 | | p+3/2=p-4/3 | | 4(y+6)=3y | | 4t-14t=40 | | -4.3-.1x=10 | | 6x=-6x | | x+4=x+1 | | -11/-11 | | (3x-0.50)=0 | | 2x^2-x+300=0 | | 4(t-6)+8t=6(2t+2)-10 | | 8(x-8)=7 | | x+x+1=329 | | 2y-6(4)=4 | | 1.6+k=-4.8 | | 2y-6(-1)=4 | | 4.4q-3.8-5.3q=-1.9q-5.3 | | 8x-20.3=x | | 5-4=6+2x | | 9x+4y=-78 | | (25b-1)-6(4b+3)=-4 | | y+4=-3 | | 3x-2=(x+3) | | ln(x+6)-ln(x-2)=ln(x) | | 8n=-16 | | p(5p+1)(5p-1)= |